Constitutive modelling of UHPCC material under impact and blast loadings. (July 2021) - Yang, Shangbin; Kong, Xiangzhen; Wu, Hao; Fang, Qin; Xiang, Hengbo
Highlights: A new dynamic tensile damage model for UHPCC material with consideration of fiber bridging mechanism is proposed and incorporated into the Kong-Fang material model. All the parameters needed in the modified Kong-Fang material model are carefully calibrated. The modified Kong-Fang material model can well predict the dynamic response and failure in UHPCC structures subjected to intensively dynamic loadings. Existing material models originally developed for traditional concrete, without carefully parameter calibration or model modification, should be cautiously used for UHPCC material. Abstract: Ultra-high performance cement based composite (UHPCC) is a prospective material for protective structures subjected to intensive loadings such as impact and blast due to its prominent dynamic mechanical properties. With the aid of an accurate material model, numerical simulation plays an increasingly important role in prediction of dynamic responses of UHPCC structures. It is known that existing concrete material models are developed for traditional concrete and cannot be applied to UHPCC material directly. In the present study, a new constitutive model of UHPCC material under impact and blast loadings is developed, which involves proposing a new tensile damage model for UHPCC which is then incorporated into the Kong-Fang material model recently developed (Int J Impact Eng 2018, 120: 60-78), and calibrating parameters of this modified material model based on existing test data. The modified material model for UHPCC is implemented into the finite element code LS-DYNA through user defined material model. Single element tests including unconfined uniaxial compression and tension and triaxial compression are firstly conducted to demonstrate the improved performances of the modified material model for UHPCC material. Then three selected experiments on UHPCC structures subjected to impact and blast loadings are numerically simulated and compared with corresponding experimental data. Numerical predictions by the modified material model are well consistent with experimental data in terms of impact force, deflection and failure.